2016
DOI: 10.1002/mawe.201600463
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of the complexation of C60 fullerene with doxorubicin in a prokaryotic model

Abstract: By means of small‐angle neutron scattering and ames mutagenicity test it was shown that C60 fullerene may act as an interceptor of the antibiotic doxorubicin by formation of a hetero‐complex with this drug. This result has been predicted based on previously developed model of chemico‐biological interaction between DNA‐binding drugs and aromatic interceptor molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…There are reports in the literature that suggest that nanostructures such as gold nanoparticles and carbon nanotubes are able to covalently interact with anticancer drugs and efficiently transport them to target cells 3,11,28,29 . On the other hand, some groups have found that nanoparticles, such as fullerene C 60 and other metal-based nanostructures, can be used as a delivery platform without interacting directly and covalently with the selected active compounds, and in consequence diminishing their biological properties 2,3,22,30,31 . To evaluate the impact of such drug-nanoparticles interactions on drugs biological activity, the bacteriological mutagenicity assay based on S. typhimurium TA98 strain can be utilized.…”
Section: Resultsmentioning
confidence: 99%
“…There are reports in the literature that suggest that nanostructures such as gold nanoparticles and carbon nanotubes are able to covalently interact with anticancer drugs and efficiently transport them to target cells 3,11,28,29 . On the other hand, some groups have found that nanoparticles, such as fullerene C 60 and other metal-based nanostructures, can be used as a delivery platform without interacting directly and covalently with the selected active compounds, and in consequence diminishing their biological properties 2,3,22,30,31 . To evaluate the impact of such drug-nanoparticles interactions on drugs biological activity, the bacteriological mutagenicity assay based on S. typhimurium TA98 strain can be utilized.…”
Section: Resultsmentioning
confidence: 99%
“…In AgNP-TBA and AgNP-MUA nanoparticles, oxidation and subsequent Ag + release can also be limited, because of their changed surface chemistry [2,3,8,10]. In the previous research conducted by our group, we repeatedly observed a modulating mechanism of different nanoparticles against tested mutagens and anticancer drugs [15,29,34,39,40]. Surprisingly, the naked AgNPs, AgNP-TBA, and AgNP-MUA, in general, do not modulate acridine mutagen activity.…”
Section: Discussionmentioning
confidence: 99%
“…In order to detect the complexation between C 60 fullerene and Dox in the aqueous solution, a range of physicochemical methods such as atomic force microscopy, UV–vis, nuclear magnetic resonance, and dynamic lights scattering spectroscopy were applied. , In particular, the small-angle neutron scattering data point out the existence of at least two statistically different entities in aqueous solution, which are the C 60 fullerene aggregates and C 60 –Dox nanocomplexes . Finally, within the proposed thermodynamic model of interaction between C 60 and Dox molecules, we calculated the equilibrium heterocomplexation constant, K L ≈ 60,000 M –1 .…”
Section: Methodsmentioning
confidence: 99%
“…35,36 In particular, the small-angle neutron scattering data point out the existence of at least two statistically different entities in aqueous solution, which are the C 60 fullerene aggregates and C 60 −Dox nanocomplexes. 37 Finally, within the proposed thermodynamic model of interaction between C 60 and Dox molecules, we calculated the equilibrium heterocomplexation constant, K L ≈ 60,000 M −1 . 38 Moreover, Dox release from the C 60 −Dox nanocomplex was evaluated by the fluorescent-based technique.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%